Effect of linear investment on nature and landscape – a case study - Lisiak, Marta; Borowiak, Klaudia; Kanclerz, Jolanta; Adamska, Anna; Szymańczyk, Janusz (Journal of Environmental Engineering and Landscape Management, 2018)
The effect of road location on natural and landscape elements is presented in this paper. Special care was focused on nature conservation areas located along three proposed road variants. Landscape metrics as a supplemental tool for selection of the most environmentally friendly road variant were here examined. The matrix method was used to analyse the potential negative effect of the road on the nature and landscape. Landscape metrics were found to be a very useful supplemental tool to evaluate the potential negative effect of the planned road on the environment. Moreover, based on our study we can also clearly relate this element to the effect on nature conservation elements. One of the most important features is the possibility to calculate certain metrics based on existing land use information without the need for field analyses, as well as obtaining specific values, which may be more objective than visual landscape assessment.